Fetal pain. - Bellieni, Carlo Valerio (Medicina e Morale, 2002)
Fetal pain is a datum of modern physiology. For many years it has been denied, as well as the fact that newborns feel pain during interventions. This behaviour was due to the fear of analgesic drugs drawbacks and to the fact that the foetus and the newborn were not considered "persons". This provoked dangerous clinical behaviours for the integrity of the central nervous system. Today, someone still denies the evidence of fetal-neonatal pain. Someone theorises it, others agree that foetuses and newborns feel pain but this does not change their clinical behaviour. Invasive procedures are very painful for the foetus. A respectful behaviour unto fetus' and premature-baby's dignity is yet possible starting from recognising their capability of suffering that we are highlighting.